The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/jca.20039
|View full text |Cite
|
Sign up to set email alerts
|

Complications of donor apheresis

Abstract: A decreasing blood donor pool in the presence of increasing blood transfusion demands has resulted in the need to maximally utilize each blood donor. This has led to a trend in the increasing use of automated blood collections. While apheresis donation shares many reactions and injuries with whole blood donation, because of the differences, unique complications also exist. Overall, evidence in the literature suggests that the frequency of reactions to apheresis donation is less than that seen in whole blood do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 63 publications
(102 reference statements)
2
79
0
5
Order By: Relevance
“…Overall, evidence in the literature suggests that the frequency of reactions to apheresis donation is less than that seen in whole blood donation. 7,8 The adverse events during the process of plateletpheresis have been broadly divided into: 5,6,8 • Venipuncture related • Syncope/sweating/faintness • Citrate reactions Pain at the site of venipuncture was noted to be more common because the same vein in one arm is used for inflow and return, resulting in trauma and hematoma to the vein. Citrate is used as primary anticoagulant in donor apheresis procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, evidence in the literature suggests that the frequency of reactions to apheresis donation is less than that seen in whole blood donation. 7,8 The adverse events during the process of plateletpheresis have been broadly divided into: 5,6,8 • Venipuncture related • Syncope/sweating/faintness • Citrate reactions Pain at the site of venipuncture was noted to be more common because the same vein in one arm is used for inflow and return, resulting in trauma and hematoma to the vein. Citrate is used as primary anticoagulant in donor apheresis procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Severe outcomes [30,43], arterial puncture [44], citrate toxicity, severe injuries to subcutaneous nerves [45,46,47,48,49,50], thrombosis of upper extremity veins [51,52], formation of an arteriovenous fistula [53,54], pseudoaneurysm [55,56,57], or compartment syndrome [58] are all extremely rare, as are some other rare events [59]. We did not see any of these rare UEs [60,61,62]. …”
Section: Discussionmentioning
confidence: 99%
“…the automated cell separators which facilitate in-line separation of cellular from plasma component and then, selective extraction of required component with the 'depleted blood' being returned back to the donors. Many authors have reported the apheresis as a safer procedure which is associated with less frequent adverse donor reactions as compared to whole blood donations [2,3]. A multi-centric study reported the frequency of adverse reactions observed in apheresis donations ranges from 0.32 to 6.81 % [4].…”
Section: Introductionmentioning
confidence: 99%
“…vasovagal reactions, hypovolemia, haematoma formation, etc. ), these are associated with few unique adverse events which are not associated with standard phlebotomies and/or whole blood donations [2,3]. These may be attributed to the usage of anticoagulant 'Acid-Citrate-Dextrose' (ACD) causing hypocalcemia and longer donation periods [4].…”
Section: Introductionmentioning
confidence: 99%